CTG repeat-targeting oligonucleotides for down-regulating Huntingtin expression. Issue 9 (17th February 2017) - Zaghloul, Eman M.; Gissberg, Olof; Moreno, Pedro M.D.; Siggens, Lee; Hällbrink, Mattias; Jørgensen, Anna S.; Ekwall, Karl; Zain, Rula; Wengel, Jesper; Lundin, Karin E.; Smith, C.I. Edvard
Abstract: Huntington's disease (HD) is a fatal, neurodegenerative disorder in which patients suffer from mobility, psychological and cognitive impairments. Existing therapeutics are only symptomatic and do not significantly alter the disease progression or increase life expectancy. HD is caused by expansion of the CAG trinucleotide repeat region in exon 1 of the Huntingtin gene ( HTT ), leading to the formation of mutant HTT transcripts (mu HTT ). The toxic gain-of-function of muHTT protein is a major cause of the disease. In addition, it has been suggested that the mu HTT transcript contributes to the toxicity. Thus, reduction of both muHTT mRNA and protein levels would ideally be the most useful therapeutic option. We herein present a novel strategy for HD treatment using oligonucleotides (ONs) directly targeting the HTT trinucleotide repeat DNA. A partial, but significant and potentially long-term, HTT knock-down of both mRNA and protein was successfully achieved. Diminished phosphorylation of HTT gene-associated RNA-polymerase II is demonstrated, suggestive of reduced transcription downstream the ON-targeted repeat. Different backbone chemistries were found to have a strong impact on the ON efficiency. We also successfully use different delivery vehicles as well as naked uptake of the ONs, demonstrating versatility and possibly providing insights for in vivo applications.